Towards the engagement of children with ADHD using Sifteo Cube Technology - Ibrahim Said Ahmad; Muhammad Aliyu, Saminu; Ahmad, Hafsa Kabir (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examines the impact of Sifteo Cube Technology in engaging children with attention deficit hyperactivity disorder (ADHD). ADHD is an early childhood neurodevelopmental disorder which starts as early as five years of age. The core symptoms are inattentiveness, impulsiveness, and hyperactivity. By identifying the history of games development and ADHD, the researchers explored the viability of using the kinesthetic technology of Sifteo Cubes to engage these children. Engaging children with ADHD can lead to better management of the children, administering of learning materials, or aid other therapeutic methods. To carry out this research, an adventure game playable on the Sifteo Cubes using open-source games development kit called Wildflower was developed and evaluated with children with ADHD for qualitative analysis. Results obtained from video capture and ethnography proved favourable. Sifteo Cubes can effectively engage the children for an average of 20 minutes. The results show that Sifteo Cubes is effective is in engaging children with ADHD.